2005
DOI: 10.1002/mnfr.200400098
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: Preventing properties against vascular alterations and ageing

Abstract: Cardiovascular diseases are the leading cause of death in developed countries where the common pathological substrate underlying this process is atherosclerosis. Several new concepts have emerged in relation to mechanisms that contribute to the regulation of the vascular diseases and associated inflammatory effects. Recently, potential antioxidants (vitamin E, polyphenols) have received much attention as potential anti-atherosclerotic agents. Among the polyphenols with health benefic properties, resveratrol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
147
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(157 citation statements)
references
References 165 publications
(176 reference statements)
4
147
0
6
Order By: Relevance
“…Epidemiological research has revealed a link between the consumption of red wine, an important source of resveratrol, and reduced risk of cardiovascular disease in France. Consequently, resveratrol has been extensively studied, and numerous beneficial effects have been observed, including antithrombotic, cardioprotective, anti-inflammatory, antioxidative, and vasorelaxant effects (Bhat et al, 2001;Delmas et al, 2005;KasdallahGrissa et al, 2007;Stef et al, 2006;). In addition, resveratrol exhibits antitumor properties in several cancer types, including prostate, mammary, colon, and lung cancers (Bhat and Pezzuto, 2002;Revel et al, 2003;Schneider et al, 2000;Stewart et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research has revealed a link between the consumption of red wine, an important source of resveratrol, and reduced risk of cardiovascular disease in France. Consequently, resveratrol has been extensively studied, and numerous beneficial effects have been observed, including antithrombotic, cardioprotective, anti-inflammatory, antioxidative, and vasorelaxant effects (Bhat et al, 2001;Delmas et al, 2005;KasdallahGrissa et al, 2007;Stef et al, 2006;). In addition, resveratrol exhibits antitumor properties in several cancer types, including prostate, mammary, colon, and lung cancers (Bhat and Pezzuto, 2002;Revel et al, 2003;Schneider et al, 2000;Stewart et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has anti-inflammatory, anti-platelet and antioxidant activities. 15 These properties of resveratrol are believed to be beneficial for the prevention and treatment of cardiovascular diseases. Resveratrol has been shown to extend the life span of a wide variety of species from yeast to mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos epidemiológicos, clínicos e in vitro mostram múl-tiplos efeitos biológicos relacionados aos compostos fenólicos da dieta, tais como: atividades antioxidante, antiinflamatória, antimicrobiana e anticarcinogênica 14,9,6,3 .…”
Section: Introductionunclassified